2003
DOI: 10.1016/s0092-8674(03)00479-3
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Tube Growth and Guidance Is Regulated by POP2, an Arabidopsis Gene that Controls GABA Levels

Abstract: During angiosperm reproduction, pollen grains form a tube that navigates through female tissues to the micropyle, delivering sperm to the egg; the signals that mediate this process are poorly understood. Here, we describe a role for gamma-amino butyric acid (GABA) in pollen tube growth and guidance. In vitro, GABA stimulates pollen tube growth, although vast excesses are inhibitory. The Arabidopsis POP2 gene encodes a transaminase that degrades GABA and contributes to the formation of a gradient leading up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
446
2
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 467 publications
(482 citation statements)
references
References 42 publications
(8 reference statements)
18
446
2
3
Order By: Relevance
“…Succinate content was reduced in flowers of both cts-1 and kat2-1, but not in cts-2. Succinic semialdehyde, which is highly reactive, could not be detected, in agreement with a previous report (Palanivelu et al, 2003).…”
Section: Gaba Metabolism In Flowers Of Cts and Kat2-1 Mutantssupporting
confidence: 93%
See 3 more Smart Citations
“…Succinate content was reduced in flowers of both cts-1 and kat2-1, but not in cts-2. Succinic semialdehyde, which is highly reactive, could not be detected, in agreement with a previous report (Palanivelu et al, 2003).…”
Section: Gaba Metabolism In Flowers Of Cts and Kat2-1 Mutantssupporting
confidence: 93%
“…Because GABA is believed to be required for correct pollen tube growth and targeting (Palanivelu et al, 2003), we tested the hypothesis that CTS and, by extension, b-oxidation, might play a role in GABA catabolism, thereby assisting the generation of a GABA gradient in reproductive tissue, which permits optimal fertility. GABA and GABA shunt metabolites (Fig.…”
Section: Gaba Metabolism In Flowers Of Cts and Kat2-1 Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Palanivelu et al revealed that GABA also plays a critical role in pollen tube growth and orientation. 6 However, whether it acts via a pathway similar to that in animal cells by binding to specific receptors and thereby triggering downstream signaling, such as the Ca 2+ /CAM pathway, is still unknown. Corresponding genes of GABA receptors have not yet been cloned, and the Arabidopsis gene bank contains no sequences homologous to the animal counterparts.…”
Section: Pleiotropic Role Of Gaba In Plant Developmentmentioning
confidence: 99%